2008
DOI: 10.1021/es801305y
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Transport and Deposition of Fullerene (C60) Nanoparticles in Quartz Sands under Varying Flow Conditions

Abstract: A coupled experimental and mathematical modeling investigation was undertaken to explore nanoscale fullerene aggregate (nC60) transport and deposition in water-saturated porous media. Column experiments were conducted with four different size fractions of Ottawa sand at two pore-water velocities. A mathematical model that incorporates nonequilibrium attachment kinetics and a maximum retention capacity was used to simulate experimental nC60 effluent breakthrough curves and deposition profiles. Fitted maximum re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
214
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(243 citation statements)
references
References 31 publications
26
214
3
Order By: Relevance
“…• Clean bed with site blocking model, where a maximum retention capacity S max was added to constrain the NPs deposition [19], given by the equations below:…”
Section: Column Studymentioning
confidence: 99%
See 2 more Smart Citations
“…• Clean bed with site blocking model, where a maximum retention capacity S max was added to constrain the NPs deposition [19], given by the equations below:…”
Section: Column Studymentioning
confidence: 99%
“…The nanoparticle deposition in porous media is conceptualized as a two-step process consisting of particle transport to the vicinity of glass beads surface, followed by attachment [19].The transport process is controlled by the models described in Section 2.5.1, while the particle attachment process is governed by the interaction forces between particle and grain surface, which is controlled by the DLVO theory.…”
Section: Derjaguin-landau-verwey-overbeek (Dlvo) Interactions Energy mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, C 60 can be made available in water as stable, nanoscale, colloidal suspensions (referred to as nC 60 herein) through various methods, such as solvent exchange, sonication, or long-term stirring without a solvent [8][9][10][11][12]. Nanoscale C 60 can be stable in aqueous environments for prolonged periods (months to years) and has a high potential for migration through soil and aquifer materials under common environmental conditions [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…However, water stable nano-aggregates of C 60 (termed nC 60 ) can be formed from pristine C 60 in certain conditions, for example, by solvent exchanging (such as tetrahydrofuran and toluene) [8], hand-grinding [9], and prelonged stirring in water [10]. As it may be a most environmentally relevant form of C 60 [11], nC 60 has recently caused much concern about its toxicity to humans and the environment, though its concentration is usually less than 10 mg/L in aquatic environment [12,13]. Although the composition and surface chemistry of nC 60 are not well understood, studies have shown that nC 60 are toxic to different biological systems, such as cells [14][15][16], bacteria [11,17,18], daphnia [19,20], and fishes [20][21][22].…”
mentioning
confidence: 99%